Recent advances in the use of Glycoprotein (GP) Ilb/Illa receptors inhibitors - Raut, Roshan; KC, Man Bahadur; Sharma, Deewakar; Rajbhandari, Sujeeb; Baidhya, Sajan G (Nepalese Heart Journal, 2006)
Glycoprotein IIb/IIIa receptors are the most common receptor subtypes on the platelet surface. During vessel injury, the sub-endothelial layer is exposed so that platelets adhere to sub-endothelial collagen via la/Ila receptor and to von Willebrand factor via glycoprotein Ib receptor. Adherent platelets are activated by ADP, 5-HT, TXA2 etc which result in the conformational change of platelets, thereby activating nearly 80,000 GP IIb/IIIa receptors on platelet surface. These activated receptors bind fibrinogen to fascilate the formation of a platelet plug.1,2